Ketoanalogue supplements reduce mortality in patients with pre-dialysis advanced diabetic kidney disease: A nationwide population-based study. Issue 6 (June 2021) - Chen, Hsing-Yu; Sun, Chiao-Yin; Lee, Chin-Chan; Wu, I-Wen; Chen, Yung-Chang; Lin, Yi-Hsuan; Fang, Wei-Ching; Pan, Heng-Chih
Summary: Background & aims: Metabolism dysregulation and protein energy wasting occur in patients with chronic kidney disease (CKD) and are associated with poor survival, especially in patients prior to starting dialysis. Accumulating evidence indicates that dietary supplementation with ketoanalogues (KAs, a mixture of branched-chain amino acids) exerts a variety of beneficial effects for patients with CKD. However, the role of KAs in diabetic kidney disease (DKD), one of the major causes of CKD, is still controversial. The aim of this study was to explore the impact of KA supplements on survival in patients with stage 5 DKD who have not yet started dialysis (DKD-5-ND). Methods: We analyzed a nationwide cohort retrieved from the National Health Insurance Research Database in Taiwan to study the long-term impact of KA supplements in patients with DKD-5-ND. We enrolled 15, 782 incident pre-dialysis DKD patients between January 1, 2004 and December 31, 2007. Landmark analysis was used to eliminate immortal bias, and overlap weighting was used to balance differences between the KA users and nonusers in the beginning. The primary study endpoint was all-cause mortality, and the occurrence of permanent dialysis (presenting the end-stage renal disease, ESRD) and major adverse cardiovascular events (MACEs) was also evaluated. All patients were followed for five years or until death. Results: The prevalence of KA usage in the DKD-5-ND patients was 6.3%. The 5-year all-cause mortality rate in the KA users was lower than that in the nonusers (34.7% vs 42.7%). After adjusting for known covariates, the KA users still had a lower risk of mortality (adjusted hazard ratio [aHR]: 0.73, 95% confidence interval [CI]: 0.66–0.82). In addition, the incidence of ESRD was also slightly lower among the KA users (90.9% for users vs 91.2% for nonusers, adjusted cause-specific hazard ratio [aCSHR]: 0.65, 95% CI: 0.61–0.69), and the occurrence of MACEs was lower (adjusted incidence rate ratios [aIRR]: 0.76, 95% CI: 0.67–0.86). Although the all-cause mortality was higher among patientsolder than 70 years (60.5% for KA users vs 46.5% for nonusers) the risk reduction seemed prominent among older patients (aHR: 0.65, 95% CI: 0.56–0.76 for patients aged ≥70 years; aHR: 0.82, 95% CI: 0.71–0.96 for patients aged < 70 years). The reduction in risks of mortality was consistent in subgroup analysis and sensitivity tests. Conclusions: The use of KA supplements seemed to be beneficial for patients with DKD-5-ND; further in-depth analysis of using KA for these patients is warranted. Highlights: Ketoanalogue supplements seems to be helpful for advanced diabetic kidney disease. The survival benefit of Ketoanalogue increases with increasing accumulative dose. Ketoanalogue prolongs renal survival in pre-dialysis diabetic kidney disease. Ketoanalogue users have lower risks of developing cardiovascular complications.